Exosomes Derived From Human Adipose-Derived Stem Cells Inhibit Lipogenesis Involving Hedgehog Signaling Pathway - Ji, Ziwan; Cai, Zhongming; Gu, Shuming; He, Yucang; Zhang, Zikai; Li, Tian; Wei, Qing; Wang, Jingping; Ke, Chen; Li, Liqun (Frontiers in Bioengineering and Biotechnology, 2021)
Since obesity impairs wound closure and adipose-derived exosomes (ADEs) regulate wound healing in clinical applications, we hypothesized that ADEs may inhibit adipogenesis of adipose-derived stem cells (ADSCs) to reduce the adverse effects of obesity on wound healing. Hedgehog (Hh) signaling has been previously shown to inhibit adipogenesis in ADSCs. The present study aimed to determine the role of ADEs in the adipogenesis of ADSCs and the Hh signaling pathway. ADSCs collected from human adipose tissues were co-cultured with ADEs and treated with an adipogenic inducer. qRT-PCR showed that ADEs could inhibit adipogenic differentiation of ADSCs and activate Hedgehog (Hh) signaling. The differences in the mRNA expression profiles of genes related to Hh signaling between the groups that were exposed to either high fat or low fat indicated that increased Hh signaling activation is necessary but not sufficient to inhibit adipogenic differentiation in the ADSC differentiation process. The Hh signaling pathway can be activated effectively by ADEs, especially during high-fat exposure after treatment with ADEs. Oil Red O staining of adipocytes suggested that ADEs inhibited not only adipogenic differentiation, but also lipogenesis in ADSCs. Overall, targeted activation of Hh signaling by ADEs reduced lipid accumulation in ADSCs and may be explored for clinical applications.